Біоремедіація як екологічно безпечний метод очищення ґрунтів від важких металів - Сакун, Антоніна Олегівна; Ліфер, Валентин Євгенович; Кутковий, Д. О.; Степацов, Е. (ГО "Міжнародна наукова гільдія", 2026)
Soil contamination by heavy metals is a serious environmental problem caused by industrial activities, mining, and intensive agriculture. Bioremediation is considered an environmentally friendly method that uses plants, microorganisms, and other biological agents to remove or neutralize toxic metals in contaminated soils. Biological approaches such as phytoremediation help reduce the concentration of heavy metals while preserving soil structure and ecological balance. Therefore, bioremediation represents a promising and sustainable strategy for restoring polluted soils and protecting environmental health.
Keywords: біоремедіація; екологія; грунти; методи очищення грунтів; важкі метали; забруднення грунтів